2012
DOI: 10.1248/cpb.60.408
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Symmetry and Biological Activities of New Symmetrical Tris(2-aminoethyl)amine Derivatives

Abstract: In terms of molecular symmetry and bioactivity, new C 3 -and C S -symmetrical derivatives based on the tris(2-aminoethyl)amine scaffold were designed and synthesized. The synthesized compounds were evaluated for antiviral activity with herpes simplex virus type 1 (HSV-1) by a plaque reduction assay and for cytotoxic activity with Vero cells. Most of the compounds showed no significant anti-HSV-1 activity, but some of the symmetrical derivatives showed high levels of cytotoxic activitiy.Key words tris(2-aminoet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Thus, the TAZ template seems to be a preferable template for antiviral compounds rather than the TAEA template, 3) because antiviral activities of most of the C S -symmetrical compounds in this study were observed at lower concentrations than those of the corresponding cytotoxicities. In addition, many trisubstituted target C S -symmetrical TAZ derivatives described in this paper showed wide ranges of antiviral (anti-HSV-1) activities.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Thus, the TAZ template seems to be a preferable template for antiviral compounds rather than the TAEA template, 3) because antiviral activities of most of the C S -symmetrical compounds in this study were observed at lower concentrations than those of the corresponding cytotoxicities. In addition, many trisubstituted target C S -symmetrical TAZ derivatives described in this paper showed wide ranges of antiviral (anti-HSV-1) activities.…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, for the purpose of preparation of designed alkoxy-amino-TAZ derivatives as our target molecules, the synthetic procedure via alkoxy-substituted chloro-TAZ is expected to be superior to the procedure via amine-substituted chloro-TAZs. Chart 2 shows the strategic point of synthetic pathways via alkoxy-chloro-TAZ derivatives (7,8) to alkoxy-amino-TAZ derivatives (3,4). Our method via alkoxy-substituted chloro-TAZ intermediates for target alkoxy-amino-TAZs consisting of stepwise nucleophilic substitutions gave moderate to excellent results as shown in Table 2.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations